2017
DOI: 10.1002/smi.2777
|View full text |Cite
|
Sign up to set email alerts
|

Converging evidence that subliminal evaluative conditioning does not affect self‐esteem or cardiovascular activity

Abstract: Self‐esteem moderates the relationship between stress and (cardiovascular) health, with low self‐esteem potentially exacerbating the impact of stressors. Boosting self‐esteem may therefore help to buffer against stress. Subliminal evaluative conditioning (SEC), which subliminally couples self‐words with positive words, has previously been successfully used to boost self‐esteem, but the existing studies are in need of replication. In this article, we aimed to replicate and extend previous SEC studies. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…Thus, during sleep—when one cannot consciously worry—as well as during daily life worrying seems to continue in an unconscious fashion, along with its physiological effects. As yet, there is also growing direct evidence that subliminal (i.e., under the awareness threshold)stressful stimuli increase activity in several physiological parameters (see reviews [ 67 , 68 , 72 ] and recently [ 73 , 74 ], but see [ 75 ]), but attempts to measure unconscious stress and show associations with physiological response in the lab and in daily life have yielded varied results, depending on the type of measurement (see [ 67 , 68 ] and recently [ 73 , 76 , 77 , 78 , 79 ]).…”
Section: The Basic Challenge Of Stress Science: Explaining Prolongmentioning
confidence: 99%
“…Thus, during sleep—when one cannot consciously worry—as well as during daily life worrying seems to continue in an unconscious fashion, along with its physiological effects. As yet, there is also growing direct evidence that subliminal (i.e., under the awareness threshold)stressful stimuli increase activity in several physiological parameters (see reviews [ 67 , 68 , 72 ] and recently [ 73 , 74 ], but see [ 75 ]), but attempts to measure unconscious stress and show associations with physiological response in the lab and in daily life have yielded varied results, depending on the type of measurement (see [ 67 , 68 ] and recently [ 73 , 76 , 77 , 78 , 79 ]).…”
Section: The Basic Challenge Of Stress Science: Explaining Prolongmentioning
confidence: 99%
“…Other studies observed similar effect modulations, although less extreme in magnitude [57,58]. These effects suggest that future studies on the clinical potential of pairing procedures, especially when intending to use categorization tasks [65,69,72,85], could benefit from closely examining how an induced processing goal might affect source valence encoding.…”
Section: Processing Goalsmentioning
confidence: 57%
“…As some authors suggest, the failures to replicate pairing effects could be due to inadequate choice of stimuli or controls [71,83,100], statistical "ceiling effects" in non-clinical populations [85], or extraneous influences when measuring pairing effects with a significant temporal delay [69]. However, replication failures may also raise more profound concerns about the validity of pairing procedures [72] and ultimately discourage further explorations of their clinical potential. We will discuss potential sources for heterogeneous findings of pairing procedures in clinically relevant domains to address these concerns and facilitate future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of self-esteem captures the feeling that one is good enough (i.e., one feels satisfied with oneself and one's abilities; Rosenberg, 1965;Self-Esteem, 2016). In addition, a study has shown that self-esteem moderates the relationship between stress and cardiovascular health, and the effects of stressors may be reduced when people have high self-esteem (Versluis & Verkuil, 2018). Moreover, the relationship between self-esteem and CVDs is reflected not only in mental health but also in the physiological aspect.…”
Section: Introductionmentioning
confidence: 99%